Alternating and sequential motion rates in older adults. Issue 3 (8th February 2013) - Pierce, John E.; Cotton, Susan; Perry, Alison
Abstract Background Alternating motion rate (AMR) and sequential motion rate (SMR) are tests of articulatory diadochokinesis that are widely used in the evaluation of motor speech. However, there are no quality normative data available for adults aged 65 years and older. Aims There were two aims: (1) to obtain a representative, normative dataset of diadochokinetic rates from adults aged 65 years and older; and (2) to examine the effects of age and gender on those rates. Methods & Procedures Seventy‐six healthy adults (65–86 years) were recruited; 45 females and 31 males. Participants were divided across two age groups (65–74 and 75–86 years) and audio‐recorded while undertaking AMR (/pa/, /ta/ and /ka/) and SMR (/pataka/). The rate of the first nine syllables for each task was measured using acoustic analysis software, and age and gender effects were examined using a series of generalized linear models. The effect of age on rate variability between groups was also assessed. Outcomes & Results Normative data were obtained for both age groups and across gender. Age was not a significant factor for any task. Males had significantly higher AMR than females (/pa/ p = 0.001, /ta/ p = 0.001, /ka/ p = 0.010). No such gender difference was found for SMR. There was no significant difference in rate variability between the age groups. Conclusions & Implications Normative values for AMR and SMR in both genders and across two older age groups were acquired. Diadochokinetic rates outside such values cannot be attributed to normal ageing, so will merit further clinical investigation.